Activation of the hypothalamic-pituitary adrenal axis in response to a verbal fluency task and associations with task performance - Becker, Linda; Schade, Ursula; Rohleder, Nicolas (PLoS ONE, 2020)
Speech fluency can be impaired in stressful situations. In this study, it was investigated whether a verbal fluency task by itself, i.e. without the presence of any further stressors, induces responses of the hypothalamic-pituitary adrenal (HPA) axis and of the sympathetic nervous system (SNS). The sample consisted of n = 85 participants (68.2% female; 33.3 ± 15.2 years) who performed two consecutive verbal fluency tasks for two minutes each. The categories were either ‘stress’ or ‘disease’ and ‘animals’ or ‘foods’ which were presented in a randomized order. Three saliva samples were collected, prior to the task (t0), immediately after (t1), and ten minutes after it (t2). Salivary α-amylase and cortisol were assessed. Furthermore, blood pressure, heart rate, and ratings of actual stress perception, level of effort, and tiredness were measured. The verbal fluency task induced a HPA axis response with a maximum cortisol level at t2 which was independent of task performance. Furthermore, perceived stress and effort, as well as tiredness increased after the task. Moreover, tiredness immediately after the task was negatively correlated with task performance. No α-amylase, blood pressure, or heart rate, and therefore SNS, responses were found. Implications for the integrated specificity model are discussed. We conclude that a verbal fluency task acts like an acute stressor that induces a cortisol and a perceived stress response without the need for further (e.g., social-evaluative) stress components. Therefore, it is a less time-consuming alternative to other stress tasks that can be used in field studies with little effort.<br
Keywords: stress response; stress task; verbal fluency; speech fluency; hypothalamic-pituitary adrenal axis; sympathetic nervous system; cortisol; α-amylase; blood pressure; heart rate

Evaluation of the socially evaluated cold-pressor group test (SECPT-G) in the general population - Becker, Linda; Schade, Ursula; Rohleder, Nicolas (PeerJ, 2019)
Background In stress research, economic instruments for introducing acute stress responses are needed. In this study, we investigated whether the socially evaluated cold-pressor group test (SECPT-G) induces salivary alpha-amylase (sAA) and/or cortisol responses in the general population and whether this is associated with anthropometric, experimental, and lifestyle factors. Methods A sample of 91 participants from the general population was recruited. Salivary cortisol and sAA levels were assessed prior to (t0), immediately after (t1), and 10 min after the SECPT-G (t2). Results A robust cortisol increase was found immediately after the SECPT-G, which further increased between t1 and t2. This was independent of most of the control variables. However, men showed a trend toward higher cortisol increases than women (p = 0.005). No sAA responses were found at all. However, sAA levels were dependent on measurement time point with highest levels between 9 pm and 9:30 pm. Participants who immersed their hands into the ice water for the maximally allowed time of 3 min showed higher sAA levels at all time points than participants who removed their hands from the water earlier. Conclusions We conclude that the SECPT-G is a good means of an acute stress test when cortisol—but not necessarily sAA—responses are intended.
Keywords: SECPT; Stress; Groups; Cortisol; Alpha-amylase; Sympathetic nervous system; HPA axis; General population; Lifestyle factors; Stress test

Spatial competition on the master-saliency map - Schade, Ursula; Meinecke Berndts, Cristina (Frontiers in Psychology, 2013)
The saliency map model (Itti and Koch, 2000) is a hierarchically structured computational model, simulating visual saliency processing. Iso-feature processing on feature maps and conspicuity maps precedes cross-dimensional signal processing on the master map, where the most salient location of the visual field is selected. This texture segmentation study focuses on a possible spatial structure on the master map. In four experiments the spatial distance between a texture irregularity in the stimulus ("target") and a cross-dimensional task irrelevant texture irregularity in the backward mask ("patch") was varied. The results show that the target-patch distance modulates target detection, and that this modulation is limited to critical distances around the target. We conclude that the signals from different feature dimensions compete on a spatial master map. There is first evidence that the critical distances increase with target eccentricity. © 2013 Schade and Meinecke.
Keywords: Critical distance; Early vision; Master map; Non-classical receptive fields; Retinal eccentricity; Saliency map; Texture segmentation

Spatial distance between target and irrelevant patch modulates detection in a texture segmentation task - Meinecke Berndts, Cristina; Schade, Ursula (Spatial vision, 2009)

Texture segmentation: Do the processing units on the saliency map increase with eccentricity? - Schade, Ursula; Meinecke Berndts, Cristina (Vision research, 2011)
The saliency map is a computational model and has been constructed for simulating human saliency processing, e.g. pop-out target detection (e.g. Itti & Koch, 2000). In this study the spatial structure on the saliency map was investigated. It is proposed that the saliency map is structured into processing units whose size is increasing with retinal eccentricity. In two experiments the distance between a target in the stimulus and an irrelevant structure in the mask was varied systematically. Our findings had two main points. Firstly, in texture segmentation tasks the saliency signals from two texture irregularities interfere, when these irregularities appear within a critical spatial distance. Second, the critical distances increase with target eccentricity. The eccentricity-dependent critical distances can be interpreted as crowding effects. It is assumed that additionally to the target eccentricity, also the strength of a saliency signal can determine the spatial area of its impairing influence. © 2010 Elsevier Ltd.
Keywords: Critical distance; Crowding; Detection; Early vision; Eccentricity; Saliency map; Texture segmentation